Ant colony optimization for unit commitment problem: article / Noor Elyliana Abu Talib - Abu Talib, Noor Elyliana (2010)
The unit commitment problem is defined as the scheduling of a set of generating units/ to be on or off to meet the demand. For a power system operated by a vertically integrated monopoly, committing units is performed centrally by the utility, and the objective is to minimize the costs while supplying all demand. In this paper, ant colony optimization (ACO) is proposed to solve unit commitment problem in power system. The ACO is a cooperative agents approach which inspired by behavior of real ant of finding the shortest path from food sources without using visual clues. These cooperating agents will cooperate to find good solutions for unit commitment. In order to fulfill the demand the related constraints is consider. The proposed approach is expected to yield minimized operational cost while supplying the load from the operated generation units. This approach is tested on 6 generation units test system over 4 stages of 24 hours period. The schedule is successfully obtained for the test system.